Pengaruh Permainan Puzzle terhadap Kemampuan Memecahkan Masalah Anak Usia 5-6 Tahun di PAUD Anakhon Hi Do Hamoraon di Au Kecamatan Parmonangan - Bella Herlina Tuty Novia Purba; Adiani Hulu; Uranus Zamili (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this study was to determine the effect of puzzle games on the problem-solving abilities of children aged 5-6 years at PAUD Anakhon Hi Do Hamoraon Di Au, Parmonangan District. The method used in this study uses a quantitative pre-experimental design research method in the form of One Shot Case Study. The population is all students of group B (aged 5-6 years) at PAUD Anakhon Hi Do Hamoraon Di Au, Parmonangan District, totaling 30 people. Data were collected using a positive closed questionnaire of 15 items. The results of data analysis show that there is a positive and significant influence of puzzle games on the problem-solving abilities of children aged 5-6 years at PAUD Anakhon Hi Do Hamoraon Di Au, Parmonangan District: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.471> rtable ( = 0.05, n = 30) = 0.361 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 2.821> ttable ( = 0.05, dk = n-2 = 28) = 2.048 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="17.49" + 0.67X. b) Regression determination coefficient test (r2) = 22.1%. Thus, Ha, namely there is an influence of puzzle games on the problem-solving abilities of children aged 5-6 years at PAUD Anakhon Hi Do Hamoraon in Au, Parmonangan District, is accepted and H0 is rejected.